Experimental Analysis of Polycaprolactone High-Resolution Fused Deposition Manufacturing-Based Electric Field-Driven Jet Deposition - Yanpu Chao; Hao Yi; Fulai Cao; Shuai Lu; Lianhui Ma (Crystals, 2022)
Polycaprolactone (PCL) scaffolds have been widely used in biological manufacturing engineering. With the expansion of the PCL application field, the manufacture of high-resolution complex microstructure PCL scaffolds is becoming a technical challenge. In this paper, a novel PCL high-resolution fused deposition 3D printing based on electric field-driven (EFD) jet deposition is proposed to manufacture PCL porous scaffold structures. The process principle of continuous cone-jet printing mode was analyzed, and an experimental system was constructed based on an electric field driven jet to carry out PCL printing experiments. The experimental studies of PCL-fused deposition under different gas pressures, electric field voltages, motion velocities and deposition heights were carried out. Analysis of the experimental results shows that there is an effective range of deposition height (H) to realize stable jet printing when the applied voltage is constant. Under the stretching of electric field force and viscous drag force (FD) with increasing movement velocities (Vs) at the same voltage and deposition height, the width of deposition lines was also gradually decreased. The width of the deposition line and the velocity of the deposition platform is approximately a quadratic curve. The bending phenomenon of deposition lines also gradually decreases with the increase of the movement velocities. According to the experiment results, a single layer linear grid structure was printed under the appropriate process parameters, with compact structure, uniform size and good straightness. The experimental results verify that the PCL porous scaffold structure can be accurately printed and manufactured.